SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN CUTI KARYAWAN (Studi Kasus PT.Duta Hadir Kuningan) - Bambang Wahyudi; Yesi Agustina (NUANSA INFORMATIKA, 2011)
Vacation form work is generally called by the term ‘cuti’. ‘Cuti’ or vacation form work provided by the company, agency or institution to its employees. The company delivers cuti as a form of refreshment for the employess to be not stressed and bored at work. Based on the interest, then the vacation form work be come a right of employees must be provided by the company. Many companies already provided the vacation form work to it’s employees, but the process of granting it is still using manual mechanisms. PT.Duta Hadir is one of the companies located in kuningan regency still use the manual way in giving the vacation of work of its employees. The process of granting the vacation runs manually, so it has many problems in entering data and delays in the licensing process itself. This decision support system using the method forward chaining. Forward chaining method is process tracking which begins by displaying a collection of data or facts that convincingly towards the final conclusion. Concept forward chaining method is first beginning of the input information (if), then to the conclusion (then) and can be modeled as follows, IF (information input), THEN (conclusion) input information, can be data, evidence, findings or observations. This application uses PHP as the programming language and MySQL as database builder, as well as the design of the built using RUP methodology. Application of decision support systems provider employee’s vacation helps Human Resources to manage employee’s vacation, and they could manage the system more effectively and efficiently.Key words :employees’ vacation, decision support system, forward chaining, Web